FACTORS INFLUENCING HANDWASHING WITH SOAP BEHAVIOR AMONG JUNIOR HIGH SCHOOL STUDENTS IN JAYA SUB-DISTRICT, ACEH JAYA DISTRICT - Karma, Taufiq; Mazkina, Mazkina (Transpublika Publisher, 2023)
Handwashing with soap is a sanitation measure involving the cleaning of hands and fingers using water and soap to remove germs and interrupt their transmission. This practice is essential as hands frequently act as vectors for pathogens, transferring germs through direct or indirect contact. This research adopts a quantitative approach. The study population comprised all sixth-grade elementary school students, totaling 54 individuals. The sampling technique employed was purposive sampling, with the sample criteria being sixth-grade elementary school students. The study's findings indicate a significant relationship between knowledge factors and handwashing with soap behavior (0.028 < 0.05) and between attitude factors and handwashing with soap behavior (0.040 < 0.05). Based on these results, it can be concluded that both knowledge and attitude significantly influence handwashing behavior. This finding underscores the importance of promoting proper handwashing practices, particularly among children who are often engaged in activities that expose them to various germs. Diseases such as respiratory infections, worm infections, and diarrhea can be effectively prevented through proper handwashing with soap. Therefore, it is recommended that elementary school students in the Jaya sub-district adopt the recommended handwashing practices.